THE URGENCY OF ANTI CORRUPTION EDUCATION FOR COLLEGES IN INDONESIA - Siska Diana Sari (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Based on Transparency International’s Corruption Perception Index (CPI) in 2015, Indonesia placed in 88 rank from 107 previously. Even though this position is a two point improvement compare to Indonesia’s position in 2014, this situation still proves that the number of corruption in Indonesia is still higher than its neighboring country such as Singapore, Malaysia and Thailand. If this condition is neglected, sooner or later, this will give every bad impact for Indonesia especially in economic sector where the investor and business people will doubt our country’s ability to create a bureaucracy. Corruption is an extraordinary crime and therefore, an extraordinary effort is needed to combat it. Indonesian Government have tried very hard to fight corruption through various way, whether it is trough restricting the law or education. This is a form of tenacity and effort of the government to suppress corruption crime. This study is meant to discuss the urgency of corruption education for colleges in Indonesia. This study is a legal study with statute and conceptual approach. The result shows that the urgency of corruption education for colleges in Indonesia is a form of effort of fortifying the young generation especially collegians as character builders, empower of character, character creators, agent of change, as well as the future leaders are hoped to be able to avoid themselves from doing any crime of corruption. This is a form of effort to eradicate corruption through preventive action. The long term purpose of the action is to grow anticorruption culture among collegians and encourage them to actively take action in the eradication of corruption in Indonesia. Keywords: Anti-Corruption education for colleges.